Age-related differences in pivoting neuromuscular control during a stepping task - Park, Kyung-Mi; Kim, Olga; Seo, Eun Young; Gemechu, Duguma Teshome; Lee, Song Joo (Springer Verlag, 2026)
Purpose Age-related physiological changes affect neuromuscular control, potentially increasing functional limitations and fall risk among older adults. The aim of this study was to investigate how age affects various aspects related to pivoting neuromuscular control during stepping tasks, such as stepping speed, pivoting instability, and entropy of time to peak electromyography (EMG) in lower extremity muscles. Methods Twenty-three healthy individuals (12 young and 11 older) participated in this study. Participants performed stepping tasks on a modified stepper that allowed pivoting motion, defined as rotational movement in the transverse plane at the knee joint (i.e., tibial rotation relative to the femur). When performing stepping tasks while controlling a pivoting motion, stepping speeds, pivoting instability, and entropy of time to peak EMG of lower extremity muscles were assessed and compared between young and older groups. Results The older group showed significantly lower stepping speed (p < 0.05), greater pivoting instability (p < 0.05), and higher entropy of time to peak EMG (p < 0.05), compared to the young group. Conclusion Older adults exhibited lower ability in pivoting neuromuscular control compared with the young individuals during the stepping task. These findings may enhance our understanding of the potential risk factors for injury associated with age-related differences in pivoting neuromuscular control.